Comparing the risk of dementia in subjects with atrial fibrillation using non-vitamin K antagonist oral anticoagulants versus vitamin K antagonists: a Belgian nationwide cohort study. - Grymonprez, Maxim; Petrovic, Mirko; Backer, Tine L De; Ikram, M Arfan; Steurbaut, Stephane; Lahousse, Lies (Age & Ageing, 2023)
Background Atrial fibrillation (AF) is associated with cognitive decline, with anticoagulated subjects potentially having a reduced risk compared with non-anticoagulated subjects. However, whether non-vitamin K antagonist oral anticoagulants (NOACs) may reduce the risk of dementia compared with vitamin K antagonists (VKAs) is unclear yet. Therefore, the risk of dementia was compared between AF subjects on NOACs versus VKAs. Methods AF subjects initiating anticoagulation between 2013 and 2019 were identified in Belgian nationwide data. Inverse probability of treatment weighted Cox regression was used to investigate cognitive outcomes. Results Among 237,012 AF subjects (310,850 person-years (PYs)), NOAC use was associated with a significantly lower risk of dementia (adjusted hazard ratio (aHR) 0.91, 95% confidence interval (CI) (0.85–0.98)) compared with VKAs. A trend towards a lower risk of vascular dementia (aHR 0.89, 95% CI (0.76–1.04)) and significantly lower risk of other/unspecified dementia (aHR 0.91, 95% CI (0.84–0.99)) were observed with NOACs compared with VKAs, whereas the risk of Alzheimer's disease was similar (aHR 0.99, 95% CI (0.88–1.11)). Apixaban (aHR 0.91, 95% CI (0.83–0.99)) and edoxaban (aHR 0.79, 95% CI (0.63–0.99)) were associated with significantly lower risks of dementia compared with VKAs, while risks were not significantly different with dabigatran (aHR 1.02, 95% CI (0.93–1.12)) and rivaroxaban (aHR 0.97, 95% CI (0.90–1.05)). Comparable risks of dementia were observed between individual NOACs, except for significantly lower risks of dementia (aHR 0.93, 95% CI (0.87–0.98)) and other/unspecified dementia (aHR 0.90 (0.84–0.97)) with apixaban compared with rivaroxaban. Conclusion NOACs were associated with a significantly lower risk of dementia compared with VKAs, likely driven by apixaban and edoxaban use.